Macrocyprididae (Ostracoda) from the Southern Ocean: taxonomic revision, macroecological patterns, and biogeographical implications - Brandão, S. N. (Zoological Journal of the Linnean Society, 2010)
Th Animal communities inhabiting shallow marine benthic environments around Antarctica are quite well known, however, only a few studies deal with the deep-water faunas in the Southern Ocean. In the present study 19 deep-water samples and 14 shallow and mid-water samples containing macrocypridids were studied. The first important finding of the present study is the fivefold increase in the diversity of Macrocyprididae in the Southern Ocean: the species count increased from six to 30. Additionally, statistical analyses showed that depth is the main factor influencing macrocypridid assemblages and that geography does not play an important role. Two faunal bathymetric boundaries were observed, one around 1250 m and the other around 2500 m depth. Furthermore, species previously believed to be widely distributed (i.e. Macroscapha opaca, Macroscapha turbida, and Macroscapha inaequata) are shown to be groups of sometimes conspicuously distinct species. Over 30 Macrocyprididae species were identified from over 1200 specimens studied. After the study of the soft part morphology and chaetotaxy of Mh. opaca under the electron microscope, the following has been observed: (1) The exopodite of antenna II is clearly inserted on the distal margin of podomere II; (2) several setae previously considered aesthetascs (i.e. the long, proximal setae of podomere IV of the antenna II; the two sexually dimorphic setae of the podomere IV of antenna II; the modified setae of the podomeres II and III of the male appendage V) lack any pore, and should therefore not be chemoreceptors. Sixteen new species are described (Macromckenziea giambonini sp. nov., Macropyxis alanlordi sp. nov., Macropyxis cronini sp. nov., Macropyxis ghartmanni sp. nov., Macropyxis hornei sp. nov., Macropyxis jeans sp. nov., Macropyxis parajeans sp. nov., Macrosarisa andeep sp. nov., Macrosarisa fahrbachi sp. nov., Macroscapha cactus sp. nov., Macroscapha falcis sp. nov., Macroscapha rehmi sp. nov., Macroscapha scotia sp. nov., Macroscapha solecavai sp. nov., Macroscapha subhemispherica sp. nov., Macroscapha walterae sp. nov.). Five previously described species are recorded: Macromckenziea glacierae Maddocks 1990, Macroscapha inaequalis (G. W. Müller, 1908), Mh. inaequata Maddocks 1990, Mh. opaca Maddocks, 1990 species complex, Mh. turbida (G. W. Müller, 1908). At least nine species are left in open nomenclature. Moreover, Yemanja gen. nov. is described from shallow tropical waters of the Western Atlantic; Macrosarisa procera (Jellinek & Swanson, 2003) comb. nov. is proposed; and Macroscapha tensa (Müller, 1908) is herein considered a nomen dubium.